Penggunaan Digital Marketing Sosial Media pada Batik SR Batam - Elvin, Elvin; Kalista, Evita; Putri, Intan Pratama; Jason, Jason; Barahama, Jonathan Miguel; Ng, Reny; Nurhaliza, Syitty; Pradana, Wahyu Ihsan; Bhalqis, Yaumil Yuninda; Kelana, Zorine (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
Social media nowadays is very important in your daily life. We can know this by how Indonesia is being the fourth largest internet user in the world. Not only in Indonesia, but social media is also being used by almost all countries around the world. Social media is are very helping human in our daily life. Social media can give us the place for socializing, building social networks, helping us getting information, as an education facility, even social media can be used as buying or selling media. The action of promotion or trading stuff by digital media or what we called social media is the definition of digital marketing. Digital marketing is one of the strategies that can be used by a small business runner or the middle business runner because digital marketing needs only a small amount of capital. Other than that, because social media nowadays is improving very fast, digital marketing can expand its range much easier.